Assessment of drainage network analysis methods to rank sediment yield hotspots. Issue 5 (4th April 2021) - Sepehri, Mehdi; Ghahramani, Afshin; Kiani-Harchegani, Mahboobeh; Ildoromi, Ali Reza; Talebi, Ali; Rodrigo-Comino, Jesús
ABSTRACT: This paper aims to test different methods used for assessing sediment yield indices to identify hotspots and rank sediment yield hotspots. This process includes the assessment of the entropy weighting (EW), fractal dimension (FD), slope length gradient (SL), and sediment connectivity (SC) methods. The indices at different sub-catchment levels were applied in the Ilanlu catchment (Iran) and organized based on five sediment hazard classes. To assess the performance of sediment hazard mapping, a method of superimposition was used and assessed with the erosion potential model (EPM). The superimposition showed that 8, 10, 4 and 9 sub-catchments, based on the degree of susceptibility, obtained the highest results from FD, EW, SL and SC, respectively, compared with the EPM model. The results show that EW and SC methods can achieve greater performance than FD and SL in identifying sediment production hotspots.